A note on Gronwall type inequality for interval-valued functions - Roman-Flores, Heriberto; Chalco-Cano, Yurilev; Silva, G. N. [UNESP]; Pedrycz, W.; Reformat, M. Z. (Ieee, 2013)
In this paper, by using the concept of gH-differentiability and Kulisch-Miranker order on intervals, we show a differential Gronwall type lemma for inteval-valued functions defined on a real compact interval T.